César Vallejo en Europa 1926-1938 / selección, cronología y postfacio Mónica Urrestarazu, Jorge Warley - Urrestarazu, MónicaWarley, Jorge; Vallejo, César (1892-1938) (Primera persona; 2)
Contiene fotografía de César Vallejo | Bibliografía: p. 89-91